Acanthagrion marinae sp. Nov. (zygoptera: Coenagrionidae): A new species of the apicale group - Lozano, Federico (2018)
Acanthagrion marinae sp. nov. (Holotype male: BRASIL, Mato Grosso do Sul, Campo Grande, UFMS, 20°29’56.26’’S-54°36’48.43’’W, 547m, leg. M.E. Rodrigues, 03.ii.2015, collection code: VZYG437, MLP) is described and illustrated on the basis of 15 males. The new species belongs to the apicale species group by having horns on S10 and sclerotized hooks on tip of distal segment of the genital ligula. It can be easily distinguished from other species of the group by a combination of characters of the genital ligulae (presence of setae on segment two; absence of setae at flexure; distal lateral lobes of segment three absent). Notes on habitat and a modification of previous keys for the species of the apicale group are provided.